2017
DOI: 10.1094/pdis-09-16-1387-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Copper-resistant Xanthomonas citri pv. citri Pathotype A Causing Asiatic Citrus Canker in Réunion, France

Abstract: CitationOpen Access.Xanthomonas citri pv. citri causes Asiatic citrus canker (ACC), which induces erumpent, callus-like lesions on all aerial organs, and consequently defoliation, premature fruit drop, and twig dieback under high inoculum pressure. Present in most tropical and subtropical citrus producing regions, the disease can lead to important decreases in yield and limitations to export markets due to the quarantine status of the pathogen in some countries (Graham et al. 2004). Strains assigned to genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
1
29
0
Order By: Relevance
“…Copper resistance, first reported in Reunion Island in 2014 (Richard et al, 2017), was detected in grove 2, but not in grove 1.…”
Section: A More Efficient Transmission Of Copperresistant Strainsmentioning
confidence: 85%
See 1 more Smart Citation
“…Copper resistance, first reported in Reunion Island in 2014 (Richard et al, 2017), was detected in grove 2, but not in grove 1.…”
Section: A More Efficient Transmission Of Copperresistant Strainsmentioning
confidence: 85%
“…The copper-resistant X. citri pv. citri strain LH201 was used as a positive control in each experiment (Richard et al, 2017).…”
Section: Cop Pcr Amplificationmentioning
confidence: 99%
“…citri copper resistance until it was discovered in the French islands of Réunion (a French territory in the South West Indian Ocean) and Martinique (a French territory in the Eastern Caribbean Sea) in 2014, two decades later (Richard et al . , ). The causative genes of Argentinian X. citri pv.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to copper‐based bactericides is also a challenge in the control of phytopathogens . Copper resistance has been observed in several phytopathogens including Pseudomonas and Xanthomonas spp . One study reported that 80% of 35 Pseudomonas syringae pv.…”
Section: Introductionmentioning
confidence: 99%